Identification and Analysis of the Tegument Protein and Excretory-Secretory Products of the Carcinogenic Liver Fluke Clonorchis sinensis - Shi, Yunliang; Yu, Kai; Liang, Anli; Huang, Yan; Ou, Fangqi; Wei, Haiyan; Wan, Xiaoling; Yang, Yichao; Zhang, Weiyu; Jiang, Zhihua (Frontiers in Microbiology, 2020)
Liver fluke proteins, including excretory-secretory products (ESPs) and tegument proteins, are critical for the pathogenesis, nutrient metabolism, etiology and immune response of liver cancer. To understand the functions of various proteins in Clonorchis sinensis physiology and human clonorchiasis, the ESPs and tegument proteins of C. sinensis were identified. Supernatants containing ESPs from adult C. sinensis after culture for 6 h were harvested and concentrated. The tegument was detached using a freeze/thaw method and successively extracted using various extraction buffers. The outer surface proteins of C. sinensis were labeled with biotin, and the biotinylated proteins were purified. The ESP, tegument and labeled outer surface proteins were identified and analyzed by high-resolution LC-MS/MS. The identified proteins were compared with those of other flukes, and the protein functions associated with pathogenesis, carcinogenesis and potential vaccine antigens and drug targets were predicted and analyzed. A total of 175 proteins were identified after the 6-h culture of C. sinensis ESPs. A total of 352 tegument proteins were identified through sequential solubilization of the isolated teguments, and a subset of these proteins were localized to the surface membrane of the tegument by labeling with biotin. Thirty identified proteins, including annexins, actin and tetraspanins, were identified as potential immunomodulators and promising vaccine antigens. Interestingly, among the 352 tegument proteins, as many as 155 were enzymes, and most were oxidoreductases, hydrolases or transferases. A comparison of the outer surface proteins of C. sinensis with those of other flukes indicated that flukes have some common outer surface proteins, such as actin, tetraspanin, glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and annexin. Granulin, thioredoxin peroxiredoxin, carbonyl reductase 1 and cystatin were identified in the C. sinensis proteome and predicted to be related to liver disease and cancer. The analysis of the C. sinensis proteome could contribute to a more in-depth understanding of complex parasite-host relationships, improve the diagnosis of clonorchiasis and benefit research on the pathogenesis and development of novel interventions, drugs and vaccines to control C. sinensis infection.